PENGARUH DESTINATION PERSONALITY TERHADAP DESTINATION LOYALTY - Nursaban Rommy; Eliyanti Agus Mokodompit; Juharsah Juharsah (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2018)
This study aims to investigate the influence of dimensions of destination personality on destination loyalty in in marine tourism of National Park Wakatobi. The number of samples are 100 respondents and survey method is used to analyze the collected data. Data analysis used multiple linear regression. These results indicate that sincerity, excitement, conviviality has significant and positive effects on destination loyalty  Keywords: destination personality, destination loyalty